1993
DOI: 10.1111/j.1464-5491.1993.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metabolism in Diabetes Mellitus: Effect of Improved Blood Glucose Control

Abstract: Reduced bone mass occurring with increased frequency in diabetes mellitus has been attributed to poor blood glucose control but the pathogenetic mechanisms remain unknown. To evaluate the role of calcium metabolism, 59 patients with diabetes and normal renal function (22 Type 1, 37 Type 2) were studied. In all patients plasma calcium (Ca), serum phosphate (PO4), serum parathyroid hormone (PTH), and 24-h urinary calcium (uCa) were determined under both poor and improved control (for at least 7 days) as ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 20 publications
4
40
0
1
Order By: Relevance
“…It has been proposed that conditions of poor metabolic control may affect bone turnover by increasing urinary calcium and phosphorus excretion. In fact, a direct relationship between fasting glucose levels and calciuria has been demonstrated [14, 15]. The resulting negative mineral balance could activate compensatory mechanisms which might result in accelerated bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that conditions of poor metabolic control may affect bone turnover by increasing urinary calcium and phosphorus excretion. In fact, a direct relationship between fasting glucose levels and calciuria has been demonstrated [14, 15]. The resulting negative mineral balance could activate compensatory mechanisms which might result in accelerated bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Although insulin resistance seems to be the main pathophysiology of the stone formation (5,7,12,16), our finding suggests that glycemic control may contribute to the risk of kidney stones independently of insulin resistance. Past studies have shown that urinary calcium excretion was positively correlated with urinary glucose excretion among diabetic subjects (17,18). It is speculated that glycosuria due to poor glycemic control increases urinary calcium levels and eventually leads to the formation of calcium stones.…”
Section: Ciationmentioning
confidence: 99%
“…A reduced bone mineral density (BMD) has been variously documented in children and adolescents with type 1 diabetes [2, 3, 4, 5, 6, 7, 8, 9, 10], but there are still conflicting data on whether it may be influenced by duration of the disease or poor metabolic control. Pathogenetic mechanisms leading to diabetic osteopenia have been alternatively ascribed either to a low turnover status, with decreased bone resorption and formation [11, 12, 13], or to a high turnover status, with increased bone resorption, hypercalciuria, and hyperphosphaturia [14, 15, 16]. We recently reported that the rate of bone resorption, evaluated by measuring the urinary excretion of the collagen cross-links pyridinoline and deoxypyridinoline (Dpyd) [17], was increased in poorly controlled children with type 1 diabetes mellitus [18].…”
Section: Introductionmentioning
confidence: 99%